Relationship Of Glycated Haemoglobin (Hba1c) And Glucose In Streptozotocininduced Wistar Rats Is Determined By Linear Regression - Simeon, George Gborienemi; Uwakwe, AA; Ibeh, GO (Asian Journal of Medical Sciences, 2013)
Objective To evaluate the relationship of glucose and glycated haemoglobin (HbA1C) in type 1 diabetes model induced by streptozotocin. Research Design and Methods Induction of diabetes mellitus was achieved through the intraperitoneal injection of 70mg/kg body weight of streptozotocin dissolved in 1m citrate buffer pH 4.5 twice daily for 2 days. A total number of thirty rats were used selected among those that have exceeded glucose threshold (>10.0mmol/l) 2 weeks after streptozotocin induction. All rats weighed between 240-300g. Samples for fasting plasma glucose and glycated haemoglobin were collected at the tail vein. Glucose was determined by the glucose oxidase method and HbA1C was determined by High Performance Liquid Chromatograph (HPLCEsi/ ms) with uv detection. Data was analysed by one way and two way analysis of variance using SPSS version. Results Significant linear relationship was demonstrated between plasma glucose level and glycated haemoglobin which could be predictive of risk of developing diabetes. Control samples had values within reference range, glucose (3.5-6.5 mmol/l) and glycated hemoglobin (4.3-7%). However diabetic test rats elicited values that varied significantly with time. Test result confirms the fact that higher mean values of plasma glucose in diabetic (positive) controls were due to the effect of streptozotocin. Conclusion Plasma glucose and glycated hemoglobin show positively mutual relationship and can be used in early diagnosis of diabetes mellitus. Using correlation coefficient and regression enhances measurement of the strength of the bivariate association and is predictive. Asian Journal of Medical Science, Volume-3 No-3 (2012), Page 1-5 DOI: http://dx.doi.org/10.3126/ajms.v3i3.4816